My eyes were closed the entire trip, but now they are open wide: A testimonio of the personal and political. Issue 3 (1st September 2020) - Gibbs, Brian
Abstract: This article is a fictionalized testimonio describing a child's crossing into the United States and her continued crossing into a political and activist high school student. The details of the story were told to me many times in conversations, writing assignments, and in discussions with her parents. Using some of her words and phrases, and with her permission, I have written the facts of the story into an imagined narrative. Taking inspiration from Anzaldua, Delgado-Bernal and Eltit this article is written in the emancipatory, creative tradition of testimonio. Particularly, Jupp, Carlderon-Berumen & O'Donald's notion of a fictionalized testimonio. Told in the first person, this testimonio describes Claudia&s memories of her physical crossing, wedged between her mother and father on a motorcycle, her success in school, and her political crossing through her fight for undocumented youth.